2022
DOI: 10.1155/2022/7942341
|View full text |Cite|
|
Sign up to set email alerts
|

Intelligent Cost Accounting Optimization System of Building Engineering Materials Based on Ant Colony Algorithm

Abstract: To save money on labour and keep track of the expenses of building engineering materials. This study provides an intelligent accounting and optimization system for building materials costs based on the ant colony algorithm. In the hardware, three relays are used to achieve open phase protection and convert the voltage signal into current signal; in the software, distinguish the material characteristics, identify the material types, use the virtual governance cost method, optimise the cost intelligent accountin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Security and Communication Networks has retracted the article titled "Intelligent Cost Accounting Optimization System of Building Engineering Materials Based on Ant Colony Algorithm" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Security and Communication Networks has retracted the article titled "Intelligent Cost Accounting Optimization System of Building Engineering Materials Based on Ant Colony Algorithm" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%